MODIFICATIONS OF VOWELS IN CONNECTED SPEECH (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article investigates vowel modifications in connected speech, a phenomenon where vowels undergo alterations to facilitate natural language flow. These modifications—vowel reduction, coarticulation, assimilation, and elision—emerge due to varying conditions such as speech rate, stress patterns, and surrounding phonetic context. This paper examines these processes, presenting examples from English and cross-linguistic perspectives, and discusses implications for language teaching and phonetic research. The findings highlight the importance of vowel modifications in achieving fluent, comprehensible speech and propose practical applications for language learners and linguists.